P774 Maintenance treatment with vedolizumab in children with Inflammatory Bowel Disease: follow-up results from the prospective multicenter VEDOKIDS study. (30th January 2023) - Atia, O; Shavit-Brunschwig, Z; Quteineh, A; Lev-Tzion, R; Stein, R; Broide, E; Urlep, D; Hyams, J; Aloi, M; Shouval, D S; Assa, A; Hussey, S; et al.
Abstract: Background: We previously reported the effectiveness of vedolizumab (VDZ) to induce remission in children with CD and UC enrolled in the prospective, multicenter VEDOKIDS study.In this extended analysis, we aimed to explore the effectiveness and safety of VDZ to maintain remission through week 30 Methods: Children with CD or UC commenced on VDZ at any stage of the disease were followed at baseline and 2, 6, 14 and 30 weeks thereafter.Explicit demographic, clinical and safety data were prospectively recorded.The primary outcome was steroid-and EEN-free clinical remission (SFR) at 30 weeks, analyzed under the ITT principle with non-response imputation.Response was defined as change of ≥ 20 points in PUCAI or >20 points in wPCDAI and clinical remission as PUCAI<10 or wPCDAI<12.5. Adverse events (AE's) were classified as severe or non-severe and related or unrelated to VDZ Results: A total of 142 children were enrolled (65 [46%] CD, 77 [54%] UC;Table).At the end of the induction period, the rates of response were 75% in UC vs 64% in CD (p=0.2), of remission 52% vs 38% (p=0.1), and of SFR 47% vs 32% (p=0.08), respectively.At week 30, SFR rates were 47% in UC and 34% in CD (p=0.1);outcomes were also numerically higher in UC, but without statistical significance(Figure) Response to induction therapy predicted week 30 remission.Of the responders, 19 (59%) children with CD and 31 (60%) with UC achieved SFR at week 30, while the corresponding figures for those not achieving response were 3 (12%; p=0.004) in CD and 5 (29%; p=0.03) in UC.Similarly, in multivariable model, response to induction treatment was highly associated with SFR at week 30, in both CD (OR 11.2 [95%CI 2.3-73]) and UC (OR 4.8 [95%CI 1.4-19]).Of the 22 patients who were responders but not remitters at week 14, four eventually achieved SFR at week 30 (1/10 [10%] in CD and 3/12 [25%] in UC) By week 30, 159 AE's were reported by 72 children including one case of Hodgkin's lymphoma (VDZ was resumed after completing the chemotherapy);the patient was never exposed to thiopurines.No cases of progressive multifocal leukoencephalopathy or deaths were reported.Thirty-six AEs in 23 (16%) children were classified as possibly related to VDZ, 11 of which (31%) were moderate and the others mild.Four children (1.4%) discontinued treatment due to AEs (one due to infusion reaction, one leukocytoclastic vasculitis, one azotemia and one due to fever and malaise Conclusion: In this prospective multicenter study, VDZ was effective for maintaining remission in children with CD, and more so in UC.Contraty to common notions, children with CD not achieving complete remission by week 14 had a very low likelihood of entering remission thereafter.Safety profile was generally good except for one lymphoma case with questionable relation to VDZ